Plasma lipoprotein(a) levels and expression of the apolipoprotein(a) gene are dependent on the nucleotide polymorphisms in its 5'-flanking region. - Suzuki, K (1997)
The apolipoprotein(a) (apo[a]) gene encodes a protein component of lipoprotein(a) [Lp(a)] whose plasma levels vary widely among individuals. Hyper-Lp(a)-emia constitutes a risk factor for thromboembolic disease. We previously subclassified the apo(a) gene into four allelic types (A-D) by polymorphisms in the 5'-flanking region. To elucidate whether these polymorphisms affect the expression of apo(a), we measured plasma Lp(a) concentrations in vivo by ELISA and examined expression of the gene by an in vitro assay using its 5'-flanking region. Homozygotes of type C had significantly higher Lp(a) levels than those of type D. The relative expression of type C was also about three times higher than that of type D, which was consistent with the in vivo results. Deletion analysis revealed that the substitution of C by T (+93) led to negative regulation in expression of the gene, while the change of G to A (+121) led to positive regulation. These results indicate that the polymorphisms in the 5'-flanking region of the apo(a) gene affect the efficiency of its expression and, in part, play a role in regulating plasma Lp(a) levels.